2013
DOI: 10.3109/00016357.2013.822551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interaction between periodontitis and type 1 diabetes mellitus on alveolar bone, mandibular condyle and tibia

Abstract: Type 1 diabetes mellitus aggravates alveolar bone loss induced by periodontitis, but periodontitis does not alter the mandibular condyle and tibia bone loss induced by diabetes. Alveolar bone, mandibular condyle and tibia may have different responses to bone loss stimuli in the diabetic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…14 When bone loss was measured, the number of sites with bone loss > 15% in poorly controlled type 1 diabetes mellitus was also 2-fold higher.Animal studies have shown that periodontal bone loss in type 1 diabetes mellitus rats increased ~3-fold compared with normal rats. 15,16 Studies of the Pima Indians provide strong evidence of the link between type 2 diabetes mellitus and periodontal disease. These studies found that the age-and sex-adjusted prevalence of periodontal disease was 60% in type 2 diabetes mellitus subjects compared with 36% in those without periodontal disease.…”
mentioning
confidence: 99%
“…14 When bone loss was measured, the number of sites with bone loss > 15% in poorly controlled type 1 diabetes mellitus was also 2-fold higher.Animal studies have shown that periodontal bone loss in type 1 diabetes mellitus rats increased ~3-fold compared with normal rats. 15,16 Studies of the Pima Indians provide strong evidence of the link between type 2 diabetes mellitus and periodontal disease. These studies found that the age-and sex-adjusted prevalence of periodontal disease was 60% in type 2 diabetes mellitus subjects compared with 36% in those without periodontal disease.…”
mentioning
confidence: 99%
“…Strong evidence indicates that poorly controlled diabetes increases susceptibility to periodontitis, also known as diabetic periodontitis [2][3][4] . Patients with diabetic periodontitis exhibit greater alveolar bone loss and a poorer prognosis after routine treatments compared with patients who do not have diabetes [5] . Furthermore, some studies have revealed that an altered host immune response results in excessive inflammation and increases the severity of periodontal tissue destruction in diabetic periodontitis [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…An association between DM and CP has been reported, and DM is regarded as a risk factor for periodontitis (Kim et al , ; Soboku et al , ; Trivedi et al , ). Dysregulated TLR expression might be involved in DM, which can exacerbate CP.…”
Section: Tlrs In Cp With Systemic Diseasesmentioning
confidence: 99%